Music Therapy and Copyright Issue: Comparative Study between Indonesia, the United States and Australia - Herlambang, Asahanna Metta Adhe; Kurniawan, Shelly (Universitas Muhammadiyah Yogyakarta, 2024)
Various factors may lead to the increase of physical and mental health problems within the society, especially among teenagers and adults. Music therapy has frequently been used to deal with such problems. Music therapy is generally conducted in private using various types of music, including musical works protected by copyright, therefore the use of music for therapeutic purpose may give rise to copyright issues. This article aims at exploring the legal frameworks on the practice of music therapy with regard to copyright issue in Indonesia and other jurisdictions. This normative juridical research employs both statutory and comparative approaches. Comparison is made with the United States and Australia. The results show that currently, there is no regulation governing music copyright used in private settings in Indonesia. Based on four factors test, the use of musical works protected by copyright in private music therapy sessions can be regarded as a fair use, provided that it is neither publicized nor distributed to the public. When music therapy sessions conducted publicly, such as performing public demonstrations with commercial purpose, therapists may use their own original songs, songs that are part of the Public Domain, musical works with a Creative Commons License, establishing an agreement with musicians, and making royalty payments to relevant institution (LMKN).